14-3-3 Proteins Are Involved in BR-Induced Ray Petal Elongation in Gerbera hybrida - Lin, Xiaohui; Huang, Shina; Huang, Gan; Chen, Yanbo; Wang, Xiaojing; Wang, Yaqin (Frontiers in Plant Science, 2021)
14-3-3 proteins play a major role in the regulation of primary metabolism, protein transport, ion channel activity, signal transduction and biotic/abiotic stress responses. However, their involvement in petal growth and development is largely unknown. Here, we identified and characterized the expression patterns of seven genes of the 14-3-3 family in gerbera. While none of the genes showed any tissue or developmental specificity of spatiotemporal expression, all seven predicted proteins have the nine α-helices typical of 14-3-3 proteins. Following treatment with brassinolide, an endogenous brassinosteroid, the Gh14-3-3 genes displayed various response patterns; for example, Gh14-3-3b and Gh14-3-3f reached their highest expression level at early (2 h) and late (24 h) timepoints, respectively. Further study revealed that overexpression of Gh14-3-3b or Gh14-3-3f promoted cell elongation, leading to an increase in ray petal length. By contrast, silencing of Gh14-3-3b or Gh14-3-3f inhibited petal elongation, which was eliminated partly by brassinolide. Correspondingly, the expression of petal elongation-related and brassinosteroid signaling-related genes was modified in transgenic petals. Taken together, our research suggests that Gh14-3-3b and Gh14-3-3f are positive regulators of brassinosteroid-induced ray petal elongation and thus provides novel insights into the molecular mechanism of petal growth and development.